Measurements of displacements and deformations and reliability analysis of Base Transceiver Station (BTS) made of steel - Skrzypczak, Izabela; Oleniacz, Grzegorz; Leń, Przemysław; Mika, Monika (International Conference “Environmental Engineering”, 2017)
Safety and reliability of Base Transceiver Station (BTS) in Global System for Mobile Communications (GSM) should be provided not only at the design stage and construction work, but also during the service. The technical conditions and safety of building structures is also dependent on the determination of geometric deviation of the entire structure and its individual components. This should be referred to the recommendations of code limits. The geodetic measurements of displacements and deformations of objects are extremely important to evaluate the stability and security of the structure and its maintenance. Steel trusses or concrete columns must meet the requirements of building standards and instructions as well as the standard requirements for the deviation limits during the construction phase and operational work. The primary and overarching objective of inventory of BTS is to ensure that the safety of the service and the users is fulfilled. The investigation of the reliability of BTS towers by determining the reliability index value using First Order Reliability Method (FORM) recommended in Eurocode 0 will be perfomed. The values of reliability index will be defined for the serviceability limit.